Correction: Robustness of performance during domain change in an esport: A study of within-expertise transfer. - Joe Thompson; Justin W O'Camb; Robin C A Barrett; Scott Harrison; Mark R Blair (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0295037.].